RAPID METHODS FOR DETECTION OF FOODBORNE PATHOGENS AND THEIR TOXINS - A REVIEW OF CURRENT TRENDS AND FUTURE PERSPECTIVES - Rozalina Yordanova; Albena Andonova (Peytchinski Publishing, 2024)
Background: Food safety is of utmost importance to sustaining life and promoting good health and is a main problem in any country, regardless of economic and social development. Unsafe food containing harmful pathogens and their toxins cause hundreds of diseases, particularly affecting infants, young children, the elderly and sick people. Therefore, the rapid detection of foodborne pathogens is of great significance for public health. The aim of this review was to provide comprehensive information regarding methods for the detection of foodborne pathogens as well as genus Fusarium and their toxins, from fundamental to state-of-the-art, presenting their advantages and limitations in order to update current knowledge. Review Results: The traditional culture-based methods for the detection of pathogens in food are usually laborious, limited by complex sample preparation procedures, time-consuming, slow to provide results, and require well-trained professional staff. However, compared to these methods, the new ones - immunological methods, nucleic acid-based assays and biosensor-based methods are rapid, accurate, highly sensitive and specific, and easy to use. Precisely providing accurate real-time results would help limit foodborne disease outbreaks, ensure compliance with legislation setting maximum levels of pathogens in certain food categories, detect and improve the import of food contaminated with dangerous levels of pathogenic microorganisms, and ensure public health safety. Conclusion: The development of rapid and automated methods that detect real-time, small numbers of viable microbial cells within a given volume of food is vital in the prevention, transmission and treatment of foodborne diseases. Such methods would also offer a great commercial advantage in the food industry and related fields